Nonlinear pedagogy in skill acquisition: An introduction - Chow, J. Y.; Davids, K.; Button, C.; Renshaw, I. (Routledge, 2016)
Nonlinear pedagogy is a powerful paradigm for understanding human movement and for designing effective teaching, coaching and training programs in sport, exercise and physical education. It addresses the inherent complexity in the learning of movement skills, viewing the learner, the learning environment and the teacher or coach as a complex interacting system, with the constraints of individual practice tasks providing the platform for functional movement behaviours to emerge. This is the first book to explain this profoundly important new approach to skill acquisition, introducing key theoretical ideas and best practice for students, teachers and coaches.